Impact of Mall Attributes on Shoppers Shopping Behavior in UB City Mall of Bengaluru City - Lakshmi Prasanna Kumari, V.; Sarveswara Reddy, A. (International Journal of Psychosocial Rehabilitation, 2021)
Malls have seen an amazing development in India among the preceding couple of years. Notwithstanding, the shopping malls have not possessed the capacity to ruthlessly give a one-stop goal to the shoppers in Bengaluru city. There is one city shopping mall considered over in this examination that speaks to the city of Bengaluru. An example of 126 respondents was taken who are the visitors of malls or those who, for the most part, buy from malls. The information was gathered through the opinions, including 34 parameters on a five-point Likert scale. A measurable examination was conducted utilizing the software SPSS version 20, which indicated exploratory factor analysis and multiple regression of data. Seven mall attributes—relaxation, entertainment, aesthetic design, accessibility, service offered at mall, mall image and shopping economy—are relevant to the shoppers shopping behavior in UB City mall were found